The girls who grew big [large type] - Mottley, Leila, 2002- (Random House Large Print Publishing, 2025)
"From the author of Nightcrawling comes a powerful new novel about a tight-knit group of teen mothers forging their own path in a small Florida town. When sixteen-year-old Adela is sent to live with her grandmother, she finds friendship and solidarity among a band of young moms who defy expectations and support one another through the trials of girlhood and motherhood. The Girls Who Grew Big is a heartfelt, hopeful story about resilience, love, and growing up on your own terms." --